Pengaruh Media Sosial Tiktok Terhadap Keputusan Berkunjung Wisatawan Pada Wisata Alam Di Kabupaten Bandung - Taufik, Muhamad Sabil Fawwazian (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p11, 2024)
Along with the development of technology and information, one of which is social media, has changed the way tourists search for information and make travel decisions. One of the popular social media platforms today is TikTok. The purpose of this study is to determine the influence of TikTok social media on tourists' decision to visit natural tourism in Bandung Regency. The method used in this research is a quantitative method with a survey technique. Data was collected through an online questionnaire distributed to tourists who have visited natural tourism in Bandung Regency. The data collected was 50 respondents. The results of this study are indicate a significant positive influence of TikTok social media on tourists' decision to visit. The calculated t-value 15.562 is greater than t-table 2.010, and the correlation coefficient (r) is 0.914. This suggests that TikTok social media has a very strong relationship with tourists' decision to visit. The coefficient of determination (R Square) is 0.835, indicating that TikTok social media influences tourists' decision to visit by 83.5%. The remaining 16.5% is influenced by other factors not examined in this study. The study concludes that individuals' decisions to visit natural attractions are also influenced by the dissemination of information, content, and testimonials through the TikTok platform. Keywords: Media Sosial,; TikTok, Keputusan Berkunjung, Wisata Alam, Kabupaten Bandung